Dependence of exhaled breath composition on exogenous factors, smoking habits and exposure to air pollutants - Filipiak, W; Ruzsanyi, V; Mochalski, P; Filipiak, A; Bajtarevic, A; Ager, C; Denz, H; Hilbe, W; Jamnig, H; Hackl, M; Dzien, A; Amann, A (Journal of breath research, 2012)
Non-invasive disease monitoring on the basis of volatile breath markers is a very attractive but challenging task. Several hundreds of compounds have been detected in exhaled air using modern analytical techniques (e.g. proton-transfer reaction mass spectrometry, gas chromatography-mass spectrometry) and have even been linked to various diseases. However,the biochemical background for most of compounds detected in breath samples has not been elucidated; therefore, the obtained results should be interpreted with care to avoid false correlations. The major aim of this study was to assess the effects of smoking on the composition of exhaled breath. Additionally, the potential origin of breath volatile organic compounds (VOCs) is discussed focusing on diet, environmental exposure and biological pathways based on other's studies. Profiles of VOCs detected in exhaled breath and inspired air samples of 115 subjects with addition of urine headspace derived from 50 volunteers are presented. Samples were analyzed with GC-MS after preconcentration on multibed sorption tubes in case of breath samples and solid phase micro-extraction (SPME) in the case of urine samples. Altogether 266 compounds were found in exhaled breath of at least 10% of the volunteers. From these, 162 compounds were identified by spectral library match and retention time (based on reference standards). It is shown that the composition of exhaled breath is considerably influenced by exposure to pollution and indoor-air contaminants and particularly by smoking. More than 80 organic compounds were found to be significantly related to smoking, the largest group comprising unsaturated hydrocarbons (29 dienes, 27 alkenes and 3 alkynes). On the basis of the presented results, we suggest that for the future understanding of breath data it will be necessary to carefully investigate the potential biological origin of volatiles, e.g., by means of analysis of tissues, isolated cell lines or other body fluids. In particular, VOCs linked to smoking habit or being the results of human exposure should be considered with care for clinical diagnosis since small changes in their concentration profiles(typically in the ppt(v)–ppb(v) range) revealing that the outbreak of certain disease might be hampered by already high background.